COVID-19 vaccination hesitancy in Italian healthcare workers: a systematic review and meta-analysis. (2nd September 2022) - Bianchi, Francesco Paolo; Stefanizzi, Pasquale; Brescia, Nazario; Lattanzio, Sabrina; Martinelli, Andrea; Tafuri, Silvio
ABSTRACT: Introduction: As for other vaccines, vaccination hesitancy may be a determining factor in the success (or otherwise) of the COVID-19 immunization campaign in healthcare workers (HCWs). Areas covered: To estimate the proportion of HCWs in Italy who expressed COVID-19 vaccine hesitancy, we conducted a systematic review of the relevant literature and a meta-analysis. Determinants of vaccine compliance and options suggested by these studies to address vaccine hesitancy among HCWs were also analyzed. Seventeen studies were included in the meta-analysis and systematic review, selected from scientific articles available in the MEDLINE/PubMed, Google Scholar and Scopus databases between 1 January 2020 and 25 January 2022. The vaccine hesitancy rate among HCWs was 13.1% (95%CI: 6.9–20.9%). The vaccine hesitancy rate among HCWs investigated before and during the vaccination campaign was 18.2% (95%CI = 12.8–24.2%) and 8.9% (95%CI = 3.4–16.6%), respectively. That main reasons for vaccine hesitation were lack of information about vaccination, opinion that the vaccine is unsafe, and fear of adverse events. Expert opinion: Despite strategies to achieve a greater willingness to immunize in this category, mandatory vaccination appears to be one of the most important measures that can guarantee the protection of HCWs and the patients they care for.